From the Five Freedoms to a more holistic perspective on animal welfare in the Dutch Animals Act - Voogt, Annika M.; Ursinus, Winanda W.; Sijm, Dick T. H. M.; Bongers, Johan H. (Frontiers in Animal Science, 2023)
One of the aims of the Dutch Animals Act is to protect animal welfare. The assumption that animal welfare risks are managed and mitigated by the Act, however, was not studied before. The aim of this paper was to evaluate whether animal welfare risks can be managed adequately under the current Animals Act and which modifications in the legislation could improve animal welfare in the Netherlands. For that purpose, welfare consequences identified in the various supply chain risk assessments from the Office of Risk Assessment & Research (BuRO) were assessed in conjunction with the Dutch Animals Acts and related legislation. A distinction was made between means- and goal-oriented legislation. The current Animals Act embraces the ‘Five Freedoms’ to define animal welfare. However, this seems outdated, given the current scientific insights that also positive experiences should be included as an integral part of animal welfare. Currently, most welfare consequences in the supply chains are linked to factors that are regulated in the Dutch legislation in qualitative, goal-oriented, open standards. Furthermore, there is no species-specific legislation for some of the most kept farm animals in the Netherlands, e.g. dairy cattle. Applying the latest scientific insights, both the current Animals Act and associated legislation can be improved to more appropriately manage animal welfare risks. As suggestion for improvement we propose that the definition of animal welfare in the Dutch Animals Act is updated, species-specific legislation for farm animals will be developed, if not yet applicable, and animal-based measures (ABMs) are integrated in legislation. As amendments to animal welfare legislation at the European level are currently developed, our proposals to include most recent scientific insights in animal welfare also hold for European legislators.